2007
DOI: 10.1002/anie.200604219
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Evidence for Nonheme Iron(III) Alkylperoxo Species as Sluggish Oxidants in Oxygenation Reactions

Abstract: The active oxidant that oxygenates organic substrates is an iron(IV) oxo intermediate, namely, [(tpa)FeIV(O)(CH3CN)]2+ (2), which is formed through OO bond homolysis, according to experimental and computational studies on the reactivity of nonheme iron(III) alkylperoxo complex [(tpa)FeIII(OOtBu)(CH3CN)]2+ (1), which was shown to be a sluggish electrophilic oxidant that is incapable of oxygenating organic substrates. tpa=tris(2‐pyridylmethyl)amine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 38 publications
7
33
0
Order By: Relevance
“…Based on spectroscopic and reactivity data, we conclude that the active species is generated by fragmentation of the alkylperoxoiron(IV) unit (Scheme 3). Indeed, this scenario is consistent with previous studies where Fe III - and Cu II -alkylperoxo complexes were found to be inert but gave rise to very reactive intermediates via O-O bond homolysis 4850…”
Section: Discussionsupporting
confidence: 92%
“…Based on spectroscopic and reactivity data, we conclude that the active species is generated by fragmentation of the alkylperoxoiron(IV) unit (Scheme 3). Indeed, this scenario is consistent with previous studies where Fe III - and Cu II -alkylperoxo complexes were found to be inert but gave rise to very reactive intermediates via O-O bond homolysis 4850…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Nam and coworkers have found [(tpa)Fe III (OOtBu)] 2+ to be unreactive with oxidizable substrates. 46 The decay of 2a and 2b was also found to be insensitive to O 2 , consistent with the complete oxidation of 1 . Upon either warming or prolonged standing in solution over the course of a few hours at −15 °C (Figures 3, and S-5 – S-7), 2a and 2b each convert to unstable EPR-silent products.…”
supporting
confidence: 56%
“…A simplified mechanistic picture for ROOH is outlined in Scheme (R=H, t Bu) 11a. 48, 49 It seems to be generally accepted that the reaction of an iron complex with ROOH first yields an iron–peroxo species [Fe III OOR] ( 11 ), which has been described as not oxidizing organic substrates and is only a precursor of the actual oxidants 50…”
Section: Resultsmentioning
confidence: 99%